Assessment of DEM accuracy generated from ALOS PRISM high resolution stereo-optical imagery using LPS - Chaminda, S. P.; Chen, Xiaoyong; Kibe, Seishiro; Samarakoon, Lal; Sri Lanka Government; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
The low resolution and high inconsistency in digital topographic data are a crucial problem of their practical usage in various engineering and scientific applications. New Japanese Panchromatic Remote sensing Instrument for Stereo Mapping (PRISM) sensor that is carried on the Advanced Land Observing Satellite (ALaS) could consider as one of the solution to overcome this topographical data quality problem. This research was initiated to assess the accuracy of ALaS generated DEM data and to evaluate the practical usage of Leica Photogrammetric Suit (LPS) software package using as a tool for generating ALOS based DEM. Study was carried out over a selected test site in Sri Lanka. Generated DEMs were compared for accuracy assessment using different Check Points (CPs). Check points were observed in the field in three distribution patterns, linear, curved and arbitrary and they were further categorized according to terrain distribution of the study area. Error maps were generated to present spatial correlation of the error distribution over the area. The lowest RMSE and NIMA Absolute Linear Error (LE)90 of the height for whole study area was 2-3 pixels depending primarily on surface roughness, vegetation and image texture and image quality. The RMSE and NIMA Absolute LE90 values of height for the specific areas ranged from 2 pixels (lowland) to 4 pixels in a tree(S1(Bcovered mountainous area. This study reveals that accuracy of the generated DEMs was significantly vary with image pair used in DEM generation, terrain type and CPs distribution patterns
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Remote Sensing and Geographical Information System
Thesis (M.Eng.) - Asian Institute of Technology, 2009
Keywords: Remote-sensing images; ALOS (Artificial satellites); Artificial satellites